Post-diagnosis serum 25-hydroxyvitamin D concentrations in women treated for breast cancer participating in a lifestyle trial in Italy - A. Fassio; G. Porciello; G. Carioli; E. Palumbo; S. Vitale; A. Luongo; C. Montagnese; M. Prete; M. Grimaldi; R. Pica; E. Rotondo; L. Falzone; et al. (PAGEPress Publications, 2024)
Objective. To report cross-sectionally serum levels of 25-hydroxyvitamin D [25(OH)D] in women living in Italy within 12 months from breast cancer (BC) diagnosis. Methods. Baseline data were obtained from 394 women diagnosed with primary BC, enrolled from 2016 to 2019 in a lifestyle trial conducted in Italy. Subjects' characteristics were compared between two 25(OH)D concentrations (hypovitaminosis D<20 and ≥20 ng/mL) with the Chi-squared test or Fisher's exact test for small-expected counts. Using multiple logistic regression-adjusted models, we estimated odds ratios (ORs) of hypovitaminosis D with 95% confidence intervals (CIs) in the total sample and in the unsupplemented subgroup. Results. Hypovitaminosis D was found in 39% of all subjects, 60% in unsupplemented subjects, and 10% in supplemented subjects. Increasing ORs of hypovitaminosis D were found with increasing body mass index, 25-30, >30, and ≥35 versus <25 kg/m2 (ORs: 2.50, 4.64, and 5.81, respectively, in the total cohort and ORs: 2.68, 5.38, and 7.08 in the unsupplemented); living in the most southern Italian region (OR 2.50, 95%CI 1.22-5.13); and with hypertriglyceridemia (OR 2.46; 95%CI 1.16-5.22), chemotherapy history (OR 1.86, 95%CI 1.03-3.38), and inversely with anti-estrogenic therapy (OR 0.43, 95%CI 0.24-0.75) in the total sample. Conclusions. Hypovitaminosis D in women recently diagnosed with BC and participating in a lifestyle trial in Italy was widespread and highest with obesity, hypertriglyceridemia, and chemotherapy use. Considering that hypovitaminosis D is a risk factor for lower efficacy of bone density treatments and possibly BC mortality, our results suggest the need to promptly address and treat vitamin D deficiency.